2018
DOI: 10.1021/acs.cgd.7b01719
|View full text |Cite
|
Sign up to set email alerts
|

Chiral LnIII(tetramethylurea)–[WV(CN)8] Coordination Chains Showing Slow Magnetic Relaxation

Abstract: We prepared a series of isostructural chiral cyanido-bridged zigzag chains [Ln­(tmu)5]­[W­(CN)8] (Ln = Gd, 1; Tb, 2; Dy, 3; Ho, 4; Er, 5; Tm, 6) using achiral tmu = tetramethylurea. Their chiral character was confirmed with single crystal X-ray diffraction and circular dichroism measurements. Magnetic studies show antiferromagnetic interactions within cyanido-bridged LnIII–WV pairs, and interchain ordering of net spins in 1, 4, and 5. It is worth to emphasize that Dy-, Er-, and Tm-based systems combine magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 90 publications
1
16
0
Order By: Relevance
“…The shortest intrachain Ln III ···W V and W V ···W V distances for 1–9 are in the ranges of 5.717(1)–5.794(1) and 10.353(1)–10.502(1) Å, respectively, while the shortest interchain Ln III ···W V and W V ···W V distances are in the ranges of 8.802(1)–8.840(1) and 9.747(1)–9.772(1) Å, respectively. Determined values of bond lengths and angles are comparable to previously described parameters for 1D amide–Ln III –W V chains. In addition, assemblies 1–9 are rare examples of 1D cyanido-bridged coordination polymers without crystallization solvent molecules and hydrogen bond networks . Additionally, these coordination polymers have a pyroelectric crystal structure, capable of generating a temporary current upon heating or cooling, in which the electric polarization is along the b -axis …”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The shortest intrachain Ln III ···W V and W V ···W V distances for 1–9 are in the ranges of 5.717(1)–5.794(1) and 10.353(1)–10.502(1) Å, respectively, while the shortest interchain Ln III ···W V and W V ···W V distances are in the ranges of 8.802(1)–8.840(1) and 9.747(1)–9.772(1) Å, respectively. Determined values of bond lengths and angles are comparable to previously described parameters for 1D amide–Ln III –W V chains. In addition, assemblies 1–9 are rare examples of 1D cyanido-bridged coordination polymers without crystallization solvent molecules and hydrogen bond networks . Additionally, these coordination polymers have a pyroelectric crystal structure, capable of generating a temporary current upon heating or cooling, in which the electric polarization is along the b -axis …”
Section: Resultssupporting
confidence: 71%
“…Interestingly, detailed analysis of records in the Cambridge Structural Database (CSD) in a search of 1D noncentrosymmetric helical Ln III –[W V (CN) 8 ] systems revealed that all previously known systems were exclusively achieved through the rational design with chiral bisoxazolines [ SS / RR -2,6-bis­[4-isopropyl-2-oxazolin-2-yl]­pyridine, SRSR / RSRS -2,6-bis­[8 H -indeno­[1,2- d ]­oxazolin-2-yl]­pyridine, and SS / RR -2,2′-(2,6-pyridinediyl)­bis­(4-isopropyl-2-oxazoline)] and by spontaneous resolution from achiral ligands ( N , N -dimethylformamide, N , N -dimethylacetamide, and N , N , N ′, N ′-tetramethylurea). , These observations suggest that helical motives in Ln III –[W V (CN) 8 ] systems can be rationally achieved using bulky achiral amides rather than by preparing them from expensive enantiopure ligands.…”
Section: Resultsmentioning
confidence: 99%
“…The ln­(τ/s) vs T –1 plot exhibited nonlinearity, indicating that the Raman process still plays a part (Figure S12). Although the process at lower frequencies is hardly appreciable in the χ″(f) vs T plot, the relaxation times obeyed the Arrhenius law above 10 K, giving a relatively high energy barrier U eff / k B of 183.14 K with a pre-exponential factor τ 0 = 6.58 × 10 –10 s. It is noted that 3 DyMo presents the highest energy barrier among all reported {Ln III –M V } (M = Mo, W) molecular nanomagnets. …”
Section: Resultsmentioning
confidence: 86%
“…Our attention focuses on the cyano-bridged heterometallic {Ln III –M V } assemblies. The combinations of trivalent lanthanide ions with octacyanometallate units would help to afford extended structures featuring different topologies. Furthermore, the overlapping between the diffuse 4d/5d orbitals of M V ions and the internal 4f orbitals of Ln III ions can sometimes generate ferromagnetic interactions, short- to long-range ferromagnetic transitions, and the coexistence of magneto-optical properties, , which are also attractive to the design of d–f nanomagnets. However, lanthanide ions tend to adopt high coordination numbers with “hard” oxygen-containing ligands, which often leads to the rapid coordination saturation by solvent molecules rather than the coordination with nitrogen-containing octacyanometallate building units.…”
Section: Introductionmentioning
confidence: 99%
“…The design, synthesis, and characterization of magnetic cyanido-bridged metal assemblies have attracted a lot of attention in materials science, especially Prussian blue analogues offering various functionalities. From the viewpoint of magnetism, the lanthanide-based metal–organic frameworks are an excellent base for the construction of multifunctional magnetic materials since most of the lanthanides reveal intrinsic magnetic and/or luminescence properties. Until now, numerous single-molecule magnets (SMMs) based on Dy III , Tb III , and Er III and much rarer examples of compounds based on Ce III , Nd III , Ho III , Tm III , and Yb III have been reported. It is also well-established that paramagnetic Dy III and Tb III compounds can emit intense and sharp visible (vis) luminescence while complexes with Nd III , Yb III , and Er III can generate near-infrared (NIR) light. These characteristics give a remarkable opportunity to combine magnetism with luminescence and even next to incorporate additional physical properties such as nonlinear optical activity, conductivity, or porosity. ,, In some rare cases, the combination of two or more different physicochemical properties resulted in new cross-effects leading to unique phenomena . This successful approach resulted in the formation of emissive SMMs with tunable light-emitting characteristics for homo- and heterometallic materials, including polycyanidometalate-based systems. , …”
Section: Introductionmentioning
confidence: 99%